Professional development of English teachers: choosing an individual strategy - Bakhmat, Liudmyla (My University, 2018)
The article deals with the issue of professional development of English teachers. Models of professional development are analyzed. Different professional development strategies are studied, including peer-coaching, study groups, action research, mentoring, etc. Building an individual strategy is defined as of hig priority. In Ukraine, seminars, webinars, workshops, training programs, internships and international training programs are available for professional growth of teachers.
Bakhmat L. Professional development of English teachers: choosing an individual strategy / L. Bakhmat // Теоретична і дидактична філологія : зб. наук. пр. - Переяслав-Хмельницький : Домбровська Я. М., 2018. – Вип. 27. – С. 4-10.
Keywords: професійний розвиток, професійний розвиток вчителів англійської мови, моделі, принципи, стратегії професійного розвитку; professional development, professional development of English teachers, models, principles, strategies of professional development; профессиональное развитие, профессиональное развитие учителей английского языка, модели, принципы, стратегии профессионального развития